Storytelling dalam Menurunkan Perilaku Agresi pada Kanak-kanak Akhir di Sekolah Dasar X Kota Bukittinggi - Feyori, Deby Putri; Ningsih, Yuninda Tria (Program Studi Bimbingan dan Konseling, 2024)
This study aims to determine the role of storytelling in reducing aggressive behavior among late elementary school-age children at SD X in Bukittinggi. The study employed an experimental design with two groups pre-test and two groups post-test. All students of SD X Bukittinggi were the subjects of the study. The Mann-Whitney test was used for data analysis, and the sample was selected randomly. The results showed that storytelling effectively reduces aggressive behavior in late elementary school-age children at SD X Bukittinggi; the alternative hypothesis (H1) was accepted, and the null hypothesis (H0) was rejected, with a statistical value of U = 0, which is less than 0.05.